2010
DOI: 10.1186/1476-0711-9-15
|View full text |Cite
|
Sign up to set email alerts
|

Hospital infection after major amputations

Abstract: The aim of the current study was to evaluate the prevalence of stump infections after major amputations of the lower extremities.Patients rehospitalized in Hospital de Base of the Medicine School in São José do Rio Preto in the period from January 2005 to January 2007 due to stump infection after major amputations of lower extremities were evaluated in a retrospective study. All the patients underwent prophylactic antibiotic therapy at the time of the surgery. The Fisher exact test was utilized for statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…Wound infection increases the morbidity and mortality associated with amputation [4]. Severe stump wound infection is a common cause of failure of amputation and results in need for stump revision or re-amputation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound infection increases the morbidity and mortality associated with amputation [4]. Severe stump wound infection is a common cause of failure of amputation and results in need for stump revision or re-amputation.…”
Section: Introductionmentioning
confidence: 99%
“…Severe stump wound infection is a common cause of failure of amputation and results in need for stump revision or re-amputation. This further surgical procedure exposes susceptible patients to the risk of operative surgical intervention and other serious complications [4,9]. Extremity amputation is a common life-saving procedure in the management of victims of natural disasters and mass casualties with severely injured limbs [5,6,14,19].…”
Section: Introductionmentioning
confidence: 99%
“…These complications also need to be judged in the context of the risks for the alternative. Infections in post-lower limb amputation wounds have ranged from 13-40% [ 9 ] with a mortality rate in some studies proving 9% for below-knee amputations and 18% for above-knee amputations [ 10 ]. Regardless of the decision to proceed with either amputation or TFA, these studies heavily emphasize the need for proper patient selection and a strong multidisciplinary team both pre- and post-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…A two year retrospective study of amputated patients showed 7.3% re-hospitalization due to stump infection. Among the re-admitted patients, MRSA was the leading pathogen causing infection and the most common cause of death 33 . The occurrence of surgical site infection with MRSA among orthopedic and transplant surgery patients is in late post-operative days compared to general surgical patients 34 .…”
Section: Discussionmentioning
confidence: 99%